The Influence of Cultural Pluralism on Women's Leadership Discourse: A Socio-Cognitive Analysis: Selected Models - Elzieny, Asmaa Muhammad Othman (Muslim English Literature, 2024)
This paper investigates the influence of cultural pluralism on women's leadership discourse employing a socio-cognitive analysis of women leaders from diverse cultural backgrounds and examines how cultural pluralism shapes their language, communication styles, and discursive approaches. The analysis is carried out on speeches of female leaders namely the previous Singaporean president Halimah Yacob, the previous British Prime Minister Theresa May. By addressing this research gap, the paper aims to deepen our comprehension of the intersectionality of culture, gender, and leadership communication, ultimately advocating for diversity and inclusion. The study adopts the Socio-Cognitive Discourse Studies (SCDS) framework. The research investigates identity formation, socialization and cultural practices within the context of leadership discourse. The analysis concentrates on interactive and interactional metadiscourse features, including transitions, hedges, boosters, self-mentions, politeness markers, humor, and rhetorical questions. The findings demonstrate that women leaders effectively influence perceptions and emotions concerning police officers and social workers through their speeches. They emphasize diversity, collaboration, and audience engagement through interactive and interactional metadiscourse. Furthermore, these speeches advocate social values, support law enforcement, and reflect positive attitudes toward social workers and the police profession. They also celebrate diversity and inclusivity through the utilization of self-mentions, attitude markers, metaphors, and cultural pluralism elements. Overall, this research contributes to both theoretical and practical domains by enhancing our understanding of the intricate interplay between culture, gender, and leadership discourse. It provides valuable insights for leaders and organizations to develop effective communication strategies that foster diversity, equity, and inclusion.